2011
DOI: 10.1007/s00192-011-1442-z
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the anatomical and symptomatic outcomes of sacrocolpopexy and posterior intravaginal slingoplasty

Abstract: ASCP and PIVS had same efficiency for the treatment of vault prolapse during the study follow-up. Both operations had good anatomical restoration for rectocele and cystocele. Moreover, PIVS also cured enterocele as an additional advantageous over ASCP. Besides, PIVS has significantly improved stress urinary incontinence, nocturia, and pelvic pain in terms of lower urinary tract symptoms compared to ASCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Brubaker et al (30) reported that Burch colposuspension performed simultaneously with ASC reduced the development of stress urinary incontinence (SUI). Similarly, Sivaslioglu et al (31) added Burch colposuspension to ASC because of the same reasons. In the present study, all patients underwent bilateral paravaginal support and primary repair if a midline fascial defect was present, and none of the patients developed a defect during a follow-up period of 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Brubaker et al (30) reported that Burch colposuspension performed simultaneously with ASC reduced the development of stress urinary incontinence (SUI). Similarly, Sivaslioglu et al (31) added Burch colposuspension to ASC because of the same reasons. In the present study, all patients underwent bilateral paravaginal support and primary repair if a midline fascial defect was present, and none of the patients developed a defect during a follow-up period of 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Many commercial kits have been introduced in the market [57]. When comparing slingoplasty with sacrocolpopexy, the same efficacy was reported for both anatomical and symptomatic improvement [58]. …”
Section: Surgical Managementmentioning
confidence: 99%
“…In particular, anterior vaginal wall prolapse may recur in 30% to 70% of patients after standard anterior colporrhaphy [18,58,84], whereas recurrence rates in the posterior compartment after posterior colporrhaphy are only 10% to 20% [85,86]. In light of these high failure rates of the anterior compartment, vaginal surgery with synthetic meshes and biological grafts has been introduced.…”
Section: Surgical Managementmentioning
confidence: 99%